MiR-144-5p, an exosomal miRNA from bone marrow-derived macrophage in type 2 diabetes, impairs bone fracture healing via targeting Smad1 - Dong Zhang; Yifan Wu; Zonghuan Li; Hairen Chen; Siyuan Huang; Chao Jian; Aixi Yu (Journal of Nanobiotechnology, 2021)
Abstract Background Patients with diabetes have an increased risk of nonunion and delayed union of fractures. Macrophages have been shown as a key player in diabetic complications. However, it remains obscure how diabetic milieu affects macrophage-derived exosomes and its implications on osteogenic differentiation of BMSCs. In this study, we aim to define the impact of diabetic milieu on macrophage-derived exosomes, role of extracellular vesicles in intercellular communication with BMSCs, and subsequent effects on osteogenic differentiation and fracture repair. Results The osteogenic potential and the ability of fracture repair of exosomes derived from diabetic bone marrow-derived macrophages (dBMDM-exos) were revealed to be lower, as compared with non-diabetic bone marrow-derived macrophages (nBMDM-exos) in vitro and in vivo. Interestingly, miR-144-5p levels were sharply elevated in dBMDM-exos and it could be transferred into BMSCs to regulate bone regeneration by targeting Smad1. In addition, the adverse effects of dBMDM-exos on the osteogenic potential and the ability of fracture repair were reversed through the suppression of miR-144-5p inhibition in vitro and vivo. Conclusions The results demonstrated an important role of exosomal miR-144-5p in bone regeneration, offering insight into developing new strategy for the improvement of fracture healing in patients with diabetes mellitus. Graphic Abstract